2014
DOI: 10.1016/j.neurobiolaging.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol replacement extends the window of opportunity for hippocampal function

Abstract: We previously reported that treating aged female rats, ovariectomized (OVX) as young adults, with acute proestrous levels of 17β estradiol (E2) increases CA1 spine density, NMDAR/AMPAR ratio, GluN2B-mediated NMDAR current, and LTP at CA3-CA1 synapses if administered by 15, but not at 19, months post-OVX, defining the critical window of opportunity. Importantly, when rats are aged with ovaries intact until OVX at 20 months, hippocampal E2 responsiveness is maintained, indicating the deficit at 19 months post-OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 66 publications
(138 reference statements)
4
38
0
Order By: Relevance
“…As such, fundamental changes may occur in the brain during chronic treatment (e.g., downregulation of ERs) that do not occur after acute treatment. On the other end of the hormonal spectrum, long-term ovariectomy decreased hippocampal neurogenesis and prevented acute E 2 from increasing cell proliferation (Tanapat et al 2005), which is consistent with the detrimental effects of long-term ovariectomy on LTP and memory discussed above Smith et al 2010;Vedder et al 2014). Collectively, these data suggest that either chronically elevated E 2 levels or long-term hormone deprivation may permanently alter the hippocampus to reduce its responsiveness to E 2 .…”
Section: Neurogenesissupporting
confidence: 70%
See 2 more Smart Citations
“…As such, fundamental changes may occur in the brain during chronic treatment (e.g., downregulation of ERs) that do not occur after acute treatment. On the other end of the hormonal spectrum, long-term ovariectomy decreased hippocampal neurogenesis and prevented acute E 2 from increasing cell proliferation (Tanapat et al 2005), which is consistent with the detrimental effects of long-term ovariectomy on LTP and memory discussed above Smith et al 2010;Vedder et al 2014). Collectively, these data suggest that either chronically elevated E 2 levels or long-term hormone deprivation may permanently alter the hippocampus to reduce its responsiveness to E 2 .…”
Section: Neurogenesissupporting
confidence: 70%
“…Importantly, this loss was not due to aging, as rats of the same age ovariectomized just 1 mo prior to E 2 treatment exhibited increased LTP in response to E 2 (Smith et al 2010). This research group also found that treatment with both acute and chronic E 2 was unable to enhance object recognition memory in rats ovariectomized for 19 mo prior to treatment (Vedder et al 2014), suggesting important parallels between the synaptic and mnemonic responsiveness to E 2 in females. Other investigators have reported similarly detrimental effects of long-term ovariectomy on the ability of chronic E 2 to enhance spatial working memory , supporting the idea that long-term hormone deprivation impairs E 2 's capacity to facilitate hippocampal synaptic plasticity and memory.…”
Section: Synaptic Plasticitymentioning
confidence: 88%
See 1 more Smart Citation
“…It is also important to note that although several studies have used gonadally intact females, the vast majority of studies to date administered exogenous hormones to ovariectomized females because removal of the ovaries eliminates the ovarian hormone fluctuations generated by the estrous cycle. In most studies, treatment was started at the time of ovariectomy or within a week afterwards, but recent data show that long periods of ovarian hormone deprivation after ovariectomy eliminate the memory-enhancing effects of E 2 on OR [16]. As such, timing of treatment to ovariectomy is an important variable for investigators to consider.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that estrogen influences synaptic plasticity in the hippocampus and that gonadectomy results in a loss of post-synaptic dendritic spines of hippocampal neurons of the CA1 region (Vedder et al, 2014). Spine density varies with the estrous cycle, peaking at the proestrous stage, shortly before ovulation, when serum estradiol concentrations are highest (Woolley and McEwen, 1992).…”
Section: Sex Differences In Ecstasy-induced Toxicitymentioning
confidence: 99%